FPGA design best practices for team-based reuse - Simpson, Philip A.; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
Covers the latest approaches and results from reconfigurable computing architectures employed in the finance domain. So-called field-programmable gate arrays (FPGAs) have already shown to outperform standard CPU- and GPU-based computing architectures by far, saving up to 99% of energy depending on the compute tasks. Renowned authors from financial mathematics, computer architecture, and finance business introduce the readers into today?s challenges in finance IT, illustrate the most advanced approaches and use cases, and present currently known methodologies for integrating FPGAs in finance systems together with latest results. The complete algorithm-to-hardware flow is covered holistically, so this book serves as a hands-on guide for IT managers, researchers, and quants/programmers who think about integrating FPGAs into their current IT systems.
Introduction -- Project Management -- Design Specification -- System Modeling -- Resource Scoping -- Design Environment -- Board Design -- Power and Thermal analysis -- Team Based Design -- RTL Design -- IP reuse -- Embedded Design -- Functional verification -- Timing Closure -- High level Design -- In System Debug -- Design Sign-off.
Electronic reproduction.
Keywords: Field programmable gate arrays -- Design; Electronic books